Factors Influencing Islamic Financial Literacy among Muslim University Students in Mataram City - Bunga Fajriati; Akhmad Jufri; Taufiq Chaidir (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the level of Islamic financial literacy and examine the influence of financial socialization, money attitude, religiosity, and income on Islamic financial literacy among Muslim students in Mataram City. This research employs a quantitative approach using a survey method. The population consists of Muslim students enrolled in public universities in Mataram City, with a sample of 150 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that the level of Islamic financial literacy among students is relatively high, with most respondents categorized as well literate and sufficiently literate. The results of hypothesis testing show that financial socialization, money attitude, and religiosity have a positive and significant effect on Islamic financial literacy, with financial socialization emerging as the most influential factor. Meanwhile, income has a positive but insignificant effect. These findings suggest that Islamic financial literacy is influenced more by non-economic factors, particularly social learning processes, individuals’ attitudes toward money, and the internalization of religious values, rather than by economic capacity. This study provides important implications for universities, families, and relevant stakeholders to strengthen Islamic financial education and socialization through value-based and socially oriented approaches